Pan-Cancer Analysis Shows Enrichment of Macrophages, Overexpression of Checkpoint Molecules, Inhibitory Cytokines, and Immune Exhaustion Signatures in EMT-High Tumors - Tiwari, Jayesh Kumar; Negi, Shloka; Kashyap, Manju; Nizamuddin, Sheikh; Singh, Amar; Khattri, Arun (Frontiers in Oncology, 2022)
Epithelial-mesenchymal transition (EMT) is a highly dynamic process that occurs under normal circumstances; however, EMT is also known to play a central role in tumor progression and metastasis. Furthermore, role of Tumor immune microenvironment (TIME) in shaping anti-cancer immunity and inducing the EMT is also well recognized. Understanding the key features of EMT is critical for the development of effective therapeutic interventions. Given the central role of EMT in immune escape, cancer progression and treatment, we have carried out a pan-cancer TIME analysis of TCGA dataset in context to EMT. We have analyzed infiltration of various immune cells, expression of multiple checkpoint molecules and cytokines, and inflammatory and immune exhaustion gene signatures in 22 cancer types from TCGA dataset. A total of 16 cancer types showed a significantly increased (p <0.001) infiltration of macrophages in EMT-high tumors (mesenchymal samples). Further, out of the 17 checkpoint molecules we analyzed, 11 showed a significant overexpression (p <0.001) in EMT-high samples of at least 10 cancer types. Analysis of cytokines showed significant enrichment of immunosuppressive cytokines–TGFB1 and IL10–in the EMT-high group of almost all cancer types. Analysis of various gene signatures showed enrichment of inflammation, exhausted CD8+ T-cells and activated stroma signatures in EMT-high tumors. In summary, our pan-cancer EMT analysis of TCGA dataset shows that the TIME of EMT-high tumors is highly immunosuppressive compared to the EMT-low (epithelial) tumors. The distinctive features of EMT-high tumors are: (i) the enrichment of tumor associated macrophages, (ii) overexpression of immune checkpoint molecules, (iii) upregulation of immune inhibitory cytokines TGFB1 and IL10 and (iv) enrichment of inflammatory and exhausted CD8+ T cells signatures. Our study shows that TIME of different EMT groups differ significantly and this would pave the way for future studies analyzing and targeting the TIME regulators for anti-cancer immunotherapy.